Thermal Degradation of PVC & Mixed Waste Plastics to Produce Mixture of Hydrocarbon Fuel - Moinuddin Sarker; Mohammad Mamunor Rashid; Muhammad Sadikur Rahman ; Mohammed Molla (Journal of Applied Chemical Science, 2012)
Experiments of combination waste plastics such as High Density Polyethylene (HDPE), Low Density Polyethylene (LDPE), Polypropylene (PP) and Polyvinyl Chloride (PVC) were carried out in a steel reactor. The thermal cracking process was carried out in temperature range of 150 ºC to 400 ºC. The principle process products are gaseous and liquid hydrocarbon fractions similar to refinery cracking products. The solid carbon residue of around 8 to 9 % of the total raw materials are similar to coal cokes and contains higher mineral contents than the other two products. Upon further analysis using gas chromatography and Mass spectrometer (GC/MS) and furrier transform infrared spectroscopy (FT-IR) of the liquid hydrocarbon fraction showed similar chemical properties to commercial gasoline and diesel products. The similarity was in the distribution of carbon chains and alkane groups. Analysis using differential scanning calorimeter (DSC) showed the calorific value is comparable as well. The thermal degradation process was shown to be efficient because it was able to convert PVC, which contains 56% chlorine to hydrocarbon products. Specific analysis was done for the identification of chlorine in the liquid hydrocarbon products, and results have shown that the liquid hydrocarbon products contained lower chlorine content than standard chlorine level allowed by EPA. Further research is being conducted on capturing and categorizing the gaseous component and the results will be submitted on the subsequent scientific papers.